Study on the High-Temperature Corrosion Behavior of Laser Cladding Coatings in Biomass Power Plant Environments - YANG Erjuan, YANG Lan, WANG Caixia, WANG Yansong, LI Yong, LIU Fuguang, LIU Gang (Cailiao Baohu, 2024)
Compared to fuels such as coal and natural gas， biomass has a lower heating value and contains a greater variety and higher concentration of corrosive media.The combustion of biomass produces a significant amount of corrosive atmospheres containing chlorine and sulfur， as well as metallic molten salts， which leads to severe high-temperature corrosion issues on the heating surfaces of biomass waste heat boilers.Although the existing technology of overlaying nickel-based corrosion-resistant alloys on the surface of pipes can significantly enhance the service life of pipelines， it suffers from numerous drawbacks， including low operational efficiency， unsuitability for on-site construction， and thermal deformation of the pipes.Inconel 625 high-temperature corrosion-resistant coatings were prepared on the surface of TP347H heat-resistant steel using two processes: conventional laser cladding and high-speed laser cladding.A comparative study was conducted on the long-term high-temperature corrosion characteristics of TP347H heat-resistant steel before and after cladding with Inconel 625 alloy.The microstructure of the coatings was characterized using scanning electron microscopy (SEM) after preparation and after 500 hours of high-temperature chloride corrosion.The corrosion resistance of TP347H heat-resistant steel was quantitatively evaluated using the weight gain method before and after coating.Results showed that under optimized process parameters， the coatings produced by both conventional and high-speed laser cladding exhibited dense microstructures， with bond strengths of 362.4 MPa and 217.3 MPa， respectively， and dilution rates of 5.4%and 0.9%.The weight gain results from corrosion tests showed that，under simulated corrosion conditions at 550 ℃，the corrosion rates of the Inconel 625 alloy coatings from laser cladding and high-speed laser cladding were approximately 17% and 8% of that of the TP347H heat-resistant steel substrate， respectively.Under simulated corrosion conditions at 650℃， the corrosion rates of the coatings were approximately 11%and 7%of that of the TP347H heat-resistant steel substrate， respectively.